Encyclopedia of Radicals in Chemistry, Biology and Materials 2012
DOI: 10.1002/9781119953678.rad050
|View full text |Cite
|
Sign up to set email alerts
|

Radical Enzymes

Abstract: Radical enzymes catalyze reactions with intermediate radicals, which are not free but bound to the enzyme. The catalytic reactions comprise generation of a radical species that initiates formation of the substrate‐derived radical, followed by conversion to the product‐related radical, and either recycling or decomposition of the initiating radical with release of the product. These characteristics are illustrated with specific radical enzymes. Ribonucleotide reductases (RNRs) use a thiyl radical to enable a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 266 publications
0
9
0
Order By: Relevance
“…4 might occur—whether it entails one electron to two electron-transducing cofactors such as a flavin or quinone, or whether it might involve sulfur radicals. There are many thiyl radicals in biology (Buckel and Golding 2006 ), including thiyl to tyrosyl transfers as in the reaction mechanism of ribonucleotide reductase (Buckel and Golding 2012 ). However, the first step in H 2 S oxidation to sulfur or polysulfide is typically a two-electron reaction (Luther 2010 ; Luther et al.…”
Section: Sulfide and A Possible Path To Water Splittingmentioning
confidence: 99%
“…4 might occur—whether it entails one electron to two electron-transducing cofactors such as a flavin or quinone, or whether it might involve sulfur radicals. There are many thiyl radicals in biology (Buckel and Golding 2006 ), including thiyl to tyrosyl transfers as in the reaction mechanism of ribonucleotide reductase (Buckel and Golding 2012 ). However, the first step in H 2 S oxidation to sulfur or polysulfide is typically a two-electron reaction (Luther 2010 ; Luther et al.…”
Section: Sulfide and A Possible Path To Water Splittingmentioning
confidence: 99%
“…Experimentally it has been shown that 1 (2). A higher energy barrier has been calculated for reaction with adenine, giving for the first time an explanation of the lack of reactivity of 1 O 2 toward adenine.…”
Section: Working Group 2: Models Of Dna Damage and Consequencesmentioning
confidence: 91%
“…Radical enzymes catalyze reactions in which species with an odd number of electrons, classically described as "free radicals", participate [2]. This area has been intensively developed in recent decades and is now a major sub-discipline of enzymology.…”
Section: Working Group 1: Radical Enzymesmentioning
confidence: 99%
“…The radicalgenerating system consists of Y296, FAD, and [4Fe-4S], whereby the initially formed FAD· Ϫ gets a proton from the water channel via E257 and T190. This system is quite different from those of other anaerobic enzymes, which use coenzyme B 12 , Sadenosylmethionine (radical SAM enzymes), ATP-driven electron transfer, or flavin-based electron bifurcation (6,14,65). The formation of FADH· in 4HBD ensures a one-electron oxidation of the substrate, which is necessary to form the allylic ketyl radical that eliminates the hydroxyl group.…”
Section: Mutationmentioning
confidence: 99%